Implementasi Strategi Pembelajaran Inovatif dalam Mentransformasi Partisipasi Aktif Siswa Kelas X Pada Mapel PAI oleh Mahasiswa PPL di MA Hasyimiyah - Abdul Khamid Nasimul Askhia; Nurul Lailatul Hidayah; Rizkiyatul Aliyah; Hibrul Umam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to describe the implementation of innovative learning strategies through the Game-Based Learning (GBL) model to enhance the active participation of tenth-grade students in Islamic Religious Education (PAI) at MA Hasyimiyah. The research is motivated by the prevalence of conventional teacher-centered learning, which results in low student engagement and enthusiasm. Employing a descriptive qualitative approach with a case study design, the research subjects included tenth-grade students at MA Hasyimiyah and Field Experience Practice (PPL) students as key informants who conducted the lessons directly. Data collection techniques included classroom observations, semi-structured interviews with PPL students, and documentation gathered during a one-month PPL period. The results indicate that the application of the GBL model utilizing digital media such as Quizizz, Wordwall, Zep Quiz, and Spinner, as well as manual media like question-and-answer cards, significantly increased learning motivation, classroom interaction, and active participation. This improvement was evidenced by students' increased confidence in expressing opinions and intensive involvement in group discussions. Although challenges such as limited infrastructure, unstable internet connections, and restricted student device access were identified, these obstacles were effectively overcome through adaptive strategies by PPL students, who modified digital games into manual formats. This study confirms that innovative and adaptive learning strategies play a crucial role in enhancing student participation levels, particularly within the context of schools with limited facilities.